2013
DOI: 10.29173/cais223
|View full text |Cite
|
Sign up to set email alerts
|

Tagging Practices on Research Oriented Social Bookmarking Sites

Abstract: This paper examines the tagging practices evident on CiteULike, a research oriented social bookmarking site for journal articles. Tagging practices were examined using standard informetric measures for analysis of bibliographic information and term use. Additionally, tags were compared to author keywords and descriptors assigned to the same article.Résumé : Cette communication examine les pratiques d'étiquetage par mots-clés qui sont utilisés sur CiteULike, un service d'étiquetage social, pour les articles de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Enabling researchers to store, search and share interesting resources, these platforms are designed on the model of Delicious, but accommodate the special requirements of academic users, i.e. managing bibliographic metadata of scientific literature Hotho, Jäschke, Schmitz, & Stumme, 2006;Kipp, 2006b;Farooq, Song, Carroll, & Giles, 2007;Hannay, 2007;Capocci & Caldarelli, 2008;Csora, Van der Heyden, & Kersten, 2009;Good, Tennis, & Wilkinson, 2009;. CiteULike was the first service to cater these specific needs.…”
Section: Social Taggingmentioning
confidence: 99%
See 2 more Smart Citations
“…Enabling researchers to store, search and share interesting resources, these platforms are designed on the model of Delicious, but accommodate the special requirements of academic users, i.e. managing bibliographic metadata of scientific literature Hotho, Jäschke, Schmitz, & Stumme, 2006;Kipp, 2006b;Farooq, Song, Carroll, & Giles, 2007;Hannay, 2007;Capocci & Caldarelli, 2008;Csora, Van der Heyden, & Kersten, 2009;Good, Tennis, & Wilkinson, 2009;. CiteULike was the first service to cater these specific needs.…”
Section: Social Taggingmentioning
confidence: 99%
“…readers', point of view on content. Social tagging offers additional metadata and adds a new user-specific dimension of indexing to the traditional perspectives of author and intermediary indexing (Kipp, 2006a(Kipp, , 2006bPeters & Stock, 2007;Stock, 2007;Peters, 2009). Readers take a different approach for indexing documents.…”
Section: Social Taggingmentioning
confidence: 99%
See 1 more Smart Citation
“…Macgregor and McCulloch (2006) compared folksonomies with controlled vocabularies and found that while social tagging systems have deficiencies originating from the absence of controlled vocabularies, the interactive and social aspects exemplified by collaborative tagging systems as well as their collective process of information management are beneficial for traditional indexing. Similarly, Kipp (2006a, 2006b, 2007) contrasted tags, author keywords, and professionally supplied descriptors for 176 entries from http://www.citeulike.org on a 7‐point scale (Frequency of tags/author keywords/Descriptor, Number of tags/keywords/descriptor per article, User vocabulary length). Results showed that although related, taggers' terminology differs from that of authors and indexers.…”
Section: Related Workmentioning
confidence: 99%